Applications of image analysis in the evaluation of carbon materials - A. Requena; E. Abreu (Revista Técnica de la Facultad de Ingeniería, 2010)
A methodology is proposed for the semiautomatic determination of the maceral composition of mineral carbon, based on an image analysis technique. The proposed methodology allows a reduction of over 70% of the time required for this determination, and provides results with a maximum standard deviation of 0.5% in the analysis of an average of 20 fields. In view of this, the maceral composition of mineral carbon could be used as a routine assay for characterization. A similar methodology is proposed for the determination of mesophase in pitch, based upon the fractional area it occupies. This determination can be made in an average of 35 fields with a maximum standard deviation of 0.5%. In addition to this, the proposed methodology can be used to report the average and distribution of mesophase diameters, which can be used to describe its formation and growth processes.